Autores fantásticos brasileiros : do diletantismo à profissionalização - Soares, Karen Isabelle (2021)
This work is divided into two parts: an academic essay and a creative text. The essay aims to analyze the current situation of fantasy literature in Brazil in face of the recent popularization of the genre, bring up the main attributes that traditional publishers seek in new authors and suggest best practices that aspiring writers can apply in order to develop such attributes. Based on the experiences of writers and publishers stated in books or media interviews, it was concluded that the main attributes are three: literary quality, nurturing of a reading audience, and professional attitude. Then, recommended improvement strategies involve improving literary quality through reading, participation in workshops and writing practice, fomenting audience using digital presence, independent publications and in-person events, and finally, demonstrating professional attitude on the internet and when introducing themselves and submitting a manuscript to the publisher. Meanwhile, the creative text is a gamebook, that is, an interactive narrative, in which the reader plays the leading role. Located within the great genre of fantastic literature, the work is inspired by the Cthulhu Mythos, by H. P. Lovecraft. It includes elements of mystery, horror and historical fantasy and contains legacy mechanics: instructions to transform the book with stickers or writing on it throughout the reading, in order to modify later readings.